2009
DOI: 10.1093/jac/dkp237
|View full text |Cite
|
Sign up to set email alerts
|

Resistant mutants of Mycobacterium tuberculosis selected in vitro do not reflect the in vivo mechanism of isoniazid resistance

Abstract: ObjectivesThe high prevalence of isoniazid-resistant Mycobacterium tuberculosis is often explained by a high mutation rate for this trait, although detailed information to support this theory is absent. We studied the development of isoniazid resistance in vitro, making use of a laboratory strain of M. tuberculosis.MethodsSpontaneous isoniazid-resistant mutants were characterized by molecular methods allowing identification of the most commonly encountered resistance-conferring mutations. Additionally, we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 52 publications
(78 reference statements)
7
73
2
Order By: Relevance
“…We observed a biphasic pattern of killing in our in vitro persistence experiment. However, we observed less bactericidal activity of Inh compared to Rif, which might be associated with tolerance of metabolically less active persisters against Inh (67)(68)(69). We also observed that polyP deficiency is associated with increased susceptibility of M. tuberculosis to both Inh and Levo, therefore, suggesting that accumulation of polyP in M. tuberculosis induces a metabolic state that enables the bacteria to persist better in the presence of drugs.…”
Section: Discussionmentioning
confidence: 60%
“…We observed a biphasic pattern of killing in our in vitro persistence experiment. However, we observed less bactericidal activity of Inh compared to Rif, which might be associated with tolerance of metabolically less active persisters against Inh (67)(68)(69). We also observed that polyP deficiency is associated with increased susceptibility of M. tuberculosis to both Inh and Levo, therefore, suggesting that accumulation of polyP in M. tuberculosis induces a metabolic state that enables the bacteria to persist better in the presence of drugs.…”
Section: Discussionmentioning
confidence: 60%
“…For instance, the predominant mutations associated with high level of drug resistance and a low or no biological cost, such as kat G S315T, rpo B S531L, rps L K43R and gyr A D94G (conferring resistance to isoniazid, rifampicin, streptomycin and fluoroquinolones respectively), are more frequently found in clinical drug‐resistant isolates (Billington et al., 1999; Bottger et al., 1998; Campbell et al., 2011; Casali et al., 2014; Gagneux, Burgos, et al., 2006; Gagneux, Long, et al., 2006; Mariam et al., 2004; Pym et al., 2002). Indeed, some of these resistance mutations do not reduce bacterial fitness in the absence of treatment (Bergval, Schuitema, Klatser, & Anthony, 2009; Huitric et al., 2006; Mariam et al., 2004). It is worth noting that MDR and XDR strains associated with outbreaks often carried these mutations explaining the successful spread of these highly drug‐resistant strains in the community (Casali et al., 2014; Cohen et al., 2015; Niehaus, Mlisana, Gandhi, Mathema, & Brust, 2015; de Vos et al., 2013).…”
Section: Fitness Cost Of Drug Resistance‐associated Mutationsmentioning
confidence: 99%
“…As demonstrated by Bergval et al. (Bergval et al., 2009), drug resistance mutation patterns of in vitro selected‐resistant mutants do not always reflect mutation profiles obtained in clinical isolates. Indeed, mutations associated with high biological cost of resistance detected in in vitro drug‐resistant mutants are rarely found in clinical drug‐resistant isolates (Bergval et al., 2009; Gagneux, Long, et al., 2006; Huitric et al., 2006).…”
Section: Fitness Cost Of Drug Resistance‐associated Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, different solvents used for extraction could be one of the possible explanations for the differences in anti-TB activities recorded in the present study. The H37Rv isolate was earlier found to be resistant against some reference drugs including rifampicin and isoniazid, in addition to some other first line and second line drugs (Bergval et al, 2009). Growth inhibition of H37Rv strains by some of the G. capitata extracts reported is an indication that this species could be used as a good anti-TB agent against drug resistant strains of M. tuberculosis.…”
Section: Anti-mycobacterial Activity Of G Capitata Extractsmentioning
confidence: 99%